Two new species of the genus Orphnebius Motschulsky, 1858 from Mindanao, Philippines (Coleoptera: Staphylinidae: Aleocharinae: Lomechusini) - Shavrin, Alexey V.; Medina, Milton Norman D. (Zootaxa, 2024)
Two new species of aleocharine genus Orphnebius Motschulsky, 1858 (Lomechusini: Myrmedoniina) from southeastern Mindanao are described and illustrated: O. (Deroleptus) barsevskisi Shavrin, sp. n. (Candalaga Mts.) and O. (Deroleptus) poncei Shavrin, sp. n. (Davao Oriental). The distributional map for all species of the genus known from Mindanao is also provided.